Islamic Religious Education Teachers’ Efforts to Foster Students’ Critical Thinking - Mutholib, Abdul; Gürel, Irmak Sude (Faculty of Education and Teacher Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2025)
Critical thinking is pivotal for 21st century learners, yet its cultivation in Islamic Religious Education classes is under examined. This qualitative field study at SMAN 1 Lumajang employed classroom observations, semi structured interviews with the principal, one teacher, and six students, alongside document analysis to explore how teachers foster students’ critical thinking. The teacher deliberately integrated discussion, Two Stay Two Stray, debate, case studies, and HOTS based assessment. These strategies stimulated students to classify, analyse, evaluate, and summarise Islamic concepts independently. Supporting factors included the teacher’s professional competence and adequate facilities; heterogeneous student abilities and limited instructional time constrained deeper reflection. Purposeful pedagogical design and a dialogic learning environment enable teachers to foster critical thinking, though structural constraints must be addressed for sustained improvement.